2017
DOI: 10.1051/matecconf/201710305004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Indoor Plant to Reduce CO2in Indoor Environment

Abstract: Abstract. Modern country strongly emphasizes on indoor air quality (IAQ) because it can effect on human health and productivity. Numerous efforts were performed to make sure that sustainability of IAQ is guaranteed. In the last 4 th decade, researchers discover that indoor plants have abilities to reduce indoor air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Indoor plant is a possible solution to modify the association between high-level CO 2 exposure and adverse health effects. Previous studies have demonstrated the abilities of an indoor plant on indoor air quality enhancement for health benefits by air pollution reduction including PM 2.5 , TVOCs, and CO 2 [8][9][10]14]. The present study findings on indoor air quality improvement are consistent with previous findings and provide further support to our previous study's conclusions [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indoor plant is a possible solution to modify the association between high-level CO 2 exposure and adverse health effects. Previous studies have demonstrated the abilities of an indoor plant on indoor air quality enhancement for health benefits by air pollution reduction including PM 2.5 , TVOCs, and CO 2 [8][9][10]14]. The present study findings on indoor air quality improvement are consistent with previous findings and provide further support to our previous study's conclusions [15].…”
Section: Discussionsupporting
confidence: 92%
“…Plant needs CO 2 to grow and propagate in the world [7]. Previous studies have reported the abilities of an indoor plant on CO 2 reduction [8][9][10]. Also, plant is one of the effective methods to sustain indoor air quality using nonmechanical and at the same time reduce energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it can be seen that the higher the ppm value obtained after smoking, the more CO levels indoor will be. However, the previous study was succesfully proofing that the spider plant can reduce 41.47% CO levels indoor from smoking ac-tivity (Suhaimi, 2017). Figure 3 describes the results of measuring CO levels indoor before and after thes pider plants addition.…”
Section: S65mentioning
confidence: 84%
“…In the indoor environment, adjusting light conditions based on the day can affect metabolic activities, directly impacting plants' potential removal of CO 2 [55]. Suhaimi et al [56] showed that the absorbed CO 2 of plants was affected by the light intensity. The absorption of CO 2 in plants increased with the increase in the light intensity.…”
Section: The Effectiveness Of Plants At Reducing Co2 and Controlling ...mentioning
confidence: 99%